BUSINESS FEASIBILITY STUDY OF ROEMAH PEMPEK - Oktavianolita, Larasati; Sutedjo, Sonny V (President University, 2024)
As an archipelago with diverse cultural and culinary riches, Indonesia has the same challenge in terms ofefforts to maintain traditional foods in the modern era. Roemah Pempek began introducing Palembangpempek through this food stall and trying to maintain all culinary traditions in Indonesia. A recent studyin 2021 proved that 87% of the population agreed and preferred local specialties. King et al.'s opinionfinding out, customers come to the pempek factory and see various pempek sold at the stall.Roemah Pempek aims to provide the best services at an affordable price while ensuring the excellent qualityof the food. The commitment to quality and authenticity of the food is the primary professional value thatensues in the desire to provide customers with a satisfactory culinary experience. Through commitment toexcellence, Roemah Pempek seeks to preserve and promote the authenticity of pempek in the face of thespread of the modern culinary industry.Keywords: Indonesia, Traditional cuisine, Pempek, Palembang